Penanaman Pendidikan Karakter Guna Membangun Kepribadian Berbangsa dan Bernegara - Dita Hermiki Rahmadona; Leli Apriani; Tensi Ariska Putri; Zelvita Dwi Rahmadayanti (IJOCE: Indonesia Journal of Civic Education, 2022)
The purpose of this study is to analyze and describe how the current form of character education is in the midst of globalization and modernization which can be seen from how the characters are shown in social media and how the form of character planting should be in the life of the nation and state. The research method used is the method of the results of the study of national journals and the analysis of the use of social media that occurs in the community. The results of the study indicate a lack of full public awareness of the importance of character education and a decline in social values ​​and character which can be seen from self-expression in social media. The conclusion of the study is that character education for each individual needs to be strengthened with good and positive character contents starting at home, through school, and in everyday life in society. Keywords: Character Education Planting